Improved Gonorrhea and Chlamydia Testing Among Men Who Have Sex With Men Living With HIV Through Implementation of Self-Collected Tests. Issue 11 (November 2021) - Park, Ina U.; Reminick, Dominique; Schapiro, Jeffrey M.; Hurley, Leo B.; Hare, Charles Brad; Slome, Sally; Flamm, Jason A.; Anderson, Alexandra; Silverberg, Michael J.; Allerton, Michael W.
Abstract : Abstract: We implemented self-collected gonorrhea/chlamydia testing in 17 medical centers in California serving men who have sex with men living with HIV. From 2012 to 2018, gonorrhea/chlamydia testing increased from 45.2% to 63.4%. Among those tested, rectal testing increased from 42.0% to 77.3%; pharyngeal testing increased from 31.0% to 79.9% (all, P trend < 0.0001). Abstract : Implementation of self-collected swabs for gonorrhea and chlamydia led to improvements in rectal and pharyngeal testing in a large managed care organization providing HIV care.